DC-SIGN+ Macrophages Control the Induction of Transplantation Tolerance - Conde, Patricia; Rodriguez, Mercedes; van der Touw, William; Jimenez, Ana; Burns, Matthew; Miller, Jennifer; Brahmachary, Manisha; Chen, Hui-ming; Boros, Peter; Rausell-Palamos, Francisco; Yun, Tae Jin; Riquelme, Paloma; et al. (Immunity (Cambridge, Mass.), 2015)
Tissue effector cells of the monocyte lineage can differentiate into different cell types with specific cell function depending on their environment. The phenotype, developmental requirements, and functional mechanisms of immune protective macrophages that mediate the induction of transplantation tolerance remain elusive. Here, we demonstrate that costimulatory blockade favored accumulation of DC-SIGN-expressing macrophages that inhibited CD8+ T cell immunity and promoted CD4+Foxp3+ Treg cell expansion in numbers. Mechanistically, that simultaneous DC-SIGN engagement by fucosylated ligands and TLR4 signaling was required for production of immunoregulatory IL-10 associated with prolonged allograft survival. Deletion of DC-SIGN-expressing macrophages in vivo, interfering with their CSF1-dependent development, or preventing the DC-SIGN signaling pathway abrogated tolerance. Together, the results provide new insights into the tolerogenic effects of costimulatory blockade and identify DC-SIGN+ suppressive macrophages as crucial mediators of immunological tolerance with the concomitant therapeutic implications in the clinic. [Display omitted] •DC-SIGN+ macrophages inhibit CD8+ T cell proliferation and expand CD4+Foxp3+ Treg•In vivo development of DC-SIGN+ macrophages is regulated by IFN-γ and CSF1•IL-10 is essential for DC-SIGN+ macrophage-mediated suppression•Simultaneous Fucose-DC-SIGN and HMGB1-TLR4 signaling is required for IL-10 production Ochando and colleagues identify and characterize a subset of monocyte-derived macrophages that develop in the allografts of transplanted organs under costimulatory blockade. These DC-SIGN-expressing recipient macrophages are required for the induction of tolerance.